Detection of spatiotemporal asymmetry in pro level soccer players - Knudsen, N. S.; Andersen, T. B. (The Journal of Strength and Conditioning Research, 2018)
Several papers have focused on change of direction (COD) asymmetry investigated through standardized tests, and used this information to provide some spatiotemporal insight during games. The aim of this study was to investigate asymmetry in the reachable areas of the players through actual position data from soccer games. Sixteen professional players from the Danish Superliga participated in this study, but 5 were excluded because of lack of participation throughout the investigated games. The reachable areas of the players were investigated at varying sprint velocities (1-7 m/s) and within varying time intervals (0.5-4 seconds). The analysis found 7 players having spatiotemporal asymmetries in their reachable areas (0.5-3%) and shift of center of reachable area (4-29 cm). Four players (LB, RB, DM, and CF) had spatiotemporal asymmetries that could be attributed to COD and thus physiological asymmetries, whereas 3 players (LCB, LW, and RW) had spatiotemporal asymmetries that might be caused by their position or by use of tactic. This type of asymmetry was named a tactical spatiotemporal asymmetry. Coaches with knowledge about spatiotemporal asymmetries can use these actively in their tactical approach using the players' asymmetries in synergy, using opponents' asymmetries or improving the existing postgame spatiotemporal analyzing tools.